Parachutes - Yang, Kelly (Katherine Tegen Books, an imprint of HarperCollins Publisher, 2020)
They're called parachutes: teenagers dropped off to live in private homes and study in the US while their wealthy parents remain in Asia. Claire Wang never thought she'd be one of them, until her parents pluck her from her privileged life in Shanghai and enroll her at a high school in California. Suddenly she finds herself living in a stranger's house, with no one to tell her what to do for the first time in her life. She soon embraces her newfound freedom, especially when the hottest and most eligible parachute, Jay, asks her out. Dani De La Cruz, Claire's new host sister, couldn't be less thrilled that her mom rented out a room to Claire. An academic and debate-team star, Dani is determined to earn her way into Yale, even if it means competing with privileged kids who are buying their way to the top. When her debate coach starts working with her privately, Dani's game plan veers unexpectedly off course. Desperately trying to avoid each other under the same roof, Dani and Claire find themselves on a collision course, intertwining in deeper and more complicated ways, as they grapple with life-altering experiences.